Sexual dysfunction as a challenge in treated breast cancer: in-depth analysis and risk assessment to improve individual outcomes - Hernández-Blanquisett, Abraham; Quintero-Carreño, Valeria; Álvarez-Londoño, Angelina; Martínez-Ávila, María Cristina; Diaz-Cáceres, Raissa (Frontiers in Oncology, 2022)
The increasing number of breast cancer survivors has led to a greater emphasis on issues related to quality of life (QoL). Up to 75% of women treated for breast cancer (BC) report sexual disorders. However, most oncologists are not trained to recognize which patients are at high-risk of developing sexual disorders. Female sexual dysfunction (FSD) is common in patients with BC; we found that patients without FSD prior to BC treatment are at risk of developing FSD after treatment. Treatment of early BC relies on the combination of chemotherapy, surgery, and radiation therapy. All these treatments have side effects or sequelae identified as high-risk factors for the development of FSD. The choice of less toxic treatments in each modality could reduce the risk of FSD in some cases, without affecting the risk of recurrence or effectiveness. A comprehensive approach of BC must consider FSD as a determinant factor of QoL in survivors.